ANALYSIS OF THE INFLUENCE OF TRUST AND BRAND IMAGE ON CONSUMER SATISFACTION IN PRODUCT PURCHASES ON THE TOKOPEDIA APPLICATION AND IMPACT ON CUSTOMER LOYALTY (Case Study on Tokopedia Customers in Lubuklinggau, South Sumatra) - Ana Yanovi; Yomeini Margareth (CV. Radja Publika, 2024)
This study aims to analyze the influence of trust and brand image on consumer satisfaction in purchasing products through the Tokopedia application, and to evaluate its impact on customer loyalty. Along with the rapid development of e-commerce in Indonesia, trust in online buying and selling platforms has become an important factor influencing consumer decisions. On the other hand, a strong brand image also contributes to forming positive perceptions regarding product and service quality. In this study, data were collected using questionnaires distributed to Tokopedia customers in Lubuklinggau, South Sumatra, with a representative sample. The analysis method used was multiple linear regression to test the relationship between variables. The results showed that both trust and brand image have a significant positive effect on customer satisfaction. Furthermore, customer satisfaction has been shown to contribute significantly to customer loyalty, indicating that satisfied consumers tend to make repeat purchases at Tokopedia. This research provides important contributions to marketing practices and strategy development to improve brand trust and image, which can ultimately support increased customer satisfaction and loyalty in this digital era. Therefore, Tokopedia marketing managers need to consider the results of this study in formulating effective policies and strategies to attract and retain customers.